BIODEGRADASI KOMPONEN KIMIA PADA LIMBAH LIGNOSELU- LOSA OLEH JAMUR PERUSAK KAYU (Biodegradation of wood chemical components in lignocellulosic wastes by whiterot fungi) - Sri Komarayati; TjuTju Nurhayati; Gusmailina Gusmailina (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
This paper reports the result of an experiment on the treatment of different forestry wastes, i.e., the sawdust of Hevea brasiliensis Pinus merkusii, Paraserianthes falcataria and the leaves of melaleuca leucodendron with Schizophyllum commune Fr for 7 weeks.The purpose of this study is to assess the effect of white-rot fungi inoculation to the decrease of chemical components like cellulose, lignin and hemicellulose.the results reveal that after treating for 7 weeks, sengon sawdust still has a very .high cellullose content of 22.55% in rubber tree sawdust, lignin and hemicellulose contents are 32.66% and 47.39%, respectively.After decreasing chemical components. Lignocellulose waste could be fermented by solid state fermentation for biogas.